2015
DOI: 10.15407/tpwj2015.02.03
|View full text |Cite
|
Sign up to set email alerts
|

Effect of titanium-containing inoculants on structure and properties of weld metal of high-strength low-alloy steels

Abstract: There is a necessity in increase of toughness and ductility indices of weld metal of high-strength low-alloy steels. Effect of inoculants on process of solidification and formation of grains of primary structure is not studied enough. Possibility of regulation of grain size of primary weld metal structure by weld metal melt inoculation with refractory titanium compounds, included into flux-cored wire was considered. Distribution of non-metallic inclusions in weld metal on size and morphology was investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…It is known that grain size of the primary structure effects the nature of g → a transformations. If nucleation of a-phase in the disperse dendrite structure starts at grain boundary in the upper area of bainite transformation, then nucleation of ferrite inside the primary grains at boundaries with non-metallic inclusions at temperatures close to bainite transformation end [2] is typical for coarser dendrites.…”
Section: Abstract : Dendrite Structure Disperse Refractory Inmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that grain size of the primary structure effects the nature of g → a transformations. If nucleation of a-phase in the disperse dendrite structure starts at grain boundary in the upper area of bainite transformation, then nucleation of ferrite inside the primary grains at boundaries with non-metallic inclusions at temperatures close to bainite transformation end [2] is typical for coarser dendrites.…”
Section: Abstract : Dendrite Structure Disperse Refractory Inmentioning
confidence: 99%
“…Metal solidification process considering effect of the refractory inoculants can be considered as a result of interaction of two competing processes, namely high-rate movement of solidification front, caused by local non-equilibrium of diffusion processes at phase interface, and effect of the inoculants on local surface tension at phase interface, which has significant effect on formation of the weld metal primary structure of HSLA steel [4].…”
Section: Abstract : Dendrite Structure Disperse Refractory Inmentioning
confidence: 99%
“…Work [10] showed that weld pool loading with TiC, SiC and ZrO 2 refractory compounds in form of the dispersoid inoculants has positive effect on morphology of primary structure grains forming at weld metal crystallization. Investigation of a relationship between inoculants influence on the primary metal structure and formation of the secondary weld microstructure was also interesting.…”
mentioning
confidence: 99%
“…The main part of studies was performed for welding low-alloyed steels. Here, precipitation of such inclusions in the form of oxides, carbides and nitrides in weld metal was considered to be the result of chemical bonding of the respective elements during solidification, whereas the inclusions proper, both of up to 1 μm size range, and close to nanosize range, were given the role of inoculators [1][2][3][4][5][6]. In other cases, formation of nonmetallic inclusions was the result of feeding nanooxides or nanocarbides into the weld pool [7][8][9].…”
mentioning
confidence: 99%